2016
DOI: 10.1111/ffe.12506
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic entropy generation in the course of the fatigue crack initiation

Abstract: Evolution of the thermodynamic entropy generation during fatigue crack initiation life of notched specimens is studied. A set of experimental results of AA7075‐T651 is examined to determine applicability of the thermodynamic entropy generation as an index of fatigue crack initiation. Entropy accumulation is calculated from hysteresis energy and temperature rise. An increasing trend of entropy accumulation with the number of cycle to failure is observed on macroscale measurements. Results also determine that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 63 publications
(130 reference statements)
1
33
0
Order By: Relevance
“…Naderi et al [19] numerically calculated the dissipative entropy by using only the mechanical work term, assuming that plastic deformation is the dominant term and the heat conduction effect is negligible, as presented in Figure 1. This assumption was also empirically verified by Imanian et al [15] and Ontiveros et al [20], In addition, the concept of entropic endurance was further confirmed by Imanian et al [15], who measured the interacting thermodynamic forces in a coupled failure mechanism, corrosion-fatigue. Summation of entropies from both mechanical work (fatigue) and chemical reactions (corrosion) contributed to the total entropic endurance at the point of fatigue failure.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Naderi et al [19] numerically calculated the dissipative entropy by using only the mechanical work term, assuming that plastic deformation is the dominant term and the heat conduction effect is negligible, as presented in Figure 1. This assumption was also empirically verified by Imanian et al [15] and Ontiveros et al [20], In addition, the concept of entropic endurance was further confirmed by Imanian et al [15], who measured the interacting thermodynamic forces in a coupled failure mechanism, corrosion-fatigue. Summation of entropies from both mechanical work (fatigue) and chemical reactions (corrosion) contributed to the total entropic endurance at the point of fatigue failure.…”
Section: Introductionmentioning
confidence: 63%
“…As described in Equation (2), thermodynamic entropy generation is computed by the bilinear equation of force and flux for each energy dissipation mode. In the fatigue damage process, mechanical work is the dominating term, as experimentally proved from previous studies [14,20,26]. Plastic strain energy is computed numerically using discrete stress-strain data.…”
Section: Entropy Calculation Processmentioning
confidence: 85%
See 2 more Smart Citations
“…The above results were obtained for steels, polymers, titanium and its alloys and aluminum alloys. It seems appropriate to apply the rules in Figures 2 and 3 and Equations (39), (40), (52) to specific polymers, composites and natural materials like seashells for example, which are characterized by high strength and wear resistance [55][56][57][58][59]. Such an application could be realized based on the model of many contact interactions between the elements of the multibody tribo-fatigue system described in [5,60].…”
Section: Experimental Verificationmentioning
confidence: 99%